Synthesis and cytotoxicity evaluation of thiazole derivatives obtained from 2-amino-4,5,6,7-tetrahydrobenzo[b]thiophene- 3-carbonitrile - Mohareb Rafat M.; Abdallah Amira E. M.; Ahmed Ebtsam A. (Acta Pharmaceutica)
Reactivity of 2-amino-4,5,6,7-tetrahydrobenzo[b]thiophene-3- carbonitrile towards thioglycolic acid resulted in thiazole derivative 1. The latter reacted with different chemical reagents to give thiazole, pyrano[2,3-d]thiazole and thiazolo[ 4,5-d]thiazole derivatives. Cytotoxicity effects of the newly synthesized products against six cancer cell lines, namely, human gastric cancer (NUGC), human colon cancer (DLD- 1), human liver cancer (HA22T and HEPG-2), human breast cancer (MCF) and nasopharyngeal carcinoma (HONE-1) as well as against a normal fibroblast cell (WI-38) were evaluated. The study showed that the 4,5,6,7 tetrahydrobenzo[ b] thiophene derivatives 6a, 7, 8a,b, 9b and 10b,c w ere t he most active compounds. Their potencies were attributed to the presence of the electron withdrawing groups.